Disaster Risk Management Strategy : Nias Livelihoods and Economic Development Program - World Bank (Washington, DC, 2013)
The North Sumatra Provincial Government has, together with the BRR (Badan Rehabilitasi dan Rekonstruksi); the Government of Indonesia (GOI) agency responsible for post tsunami reconstruction and the Nias local government, requested support from the Multi-Donor Fund (MDF) for the proposed Nias Livelihood and Economic Development Program (LEDP). The World Bank is the partner agency. The objective of this assignment is to support the development of a disaster risk management (DRM) strategy for the Nias LEDP project to ensure that risk reduction is mainstreamed into project design, especially the livelihoods and civil works, access components. To achieve the above objective, this report identifies the key principles of DRM relevant to the LEDP, presents the results of a high-level assessment of the hazards potentially relevant to Nias and the LEDP, and outlines the risk reduction approaches that can be incorporated into the overall program and its components. This report presents a framework for the DRM Strategy to be incorporated into the proposed LEDP.